1978
DOI: 10.1042/bj1710803
|View full text |Cite
|
Sign up to set email alerts
|

Purification and some properties of an alkaline proteinase from rat skeletal muscle

Abstract: 1. Rat skeletal muscle was homogenized in 0.05M-Tris/HCl, pH 8.5, containing 1M-KCl. Myofibrillar proteins were precipitated by addition of (NH4)2SO4 (33% saturation). 2. The alkaline proteolytic activity that was precipitated with the myofibrillar proteins was solubilized with trypsin (conjugated to Sepharose) and further purified by affinity chromatography, ion-exchange chromatography and gel filtration. 3. The purified enzyme migrates as a single band in polyacrylamide-disc electrophoresis, and has optimum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1979
1979
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Rat skeletal-muscle homogenates exhibit appreciable proteolytic activity at alkaline-pH values (Koszalka & Miller, 1960). Several groups have proposed that this alkaline activity, which may consist of one or more enzymes, plays a role in breakdown of myofibrillar protein (Noguchi & Kandatsu, 1971;Mayer et al, 1974;Dahlmann & Reinauer, 1978). The so-called 'group-specific proteinase' in skeletal muscle resembles this activity as well (Banno et al, 1975).…”
Section: Effects Ofproteinase Inhibitors On Protein Turnover In Intact Musclesmentioning
confidence: 99%
“…Rat skeletal-muscle homogenates exhibit appreciable proteolytic activity at alkaline-pH values (Koszalka & Miller, 1960). Several groups have proposed that this alkaline activity, which may consist of one or more enzymes, plays a role in breakdown of myofibrillar protein (Noguchi & Kandatsu, 1971;Mayer et al, 1974;Dahlmann & Reinauer, 1978). The so-called 'group-specific proteinase' in skeletal muscle resembles this activity as well (Banno et al, 1975).…”
Section: Effects Ofproteinase Inhibitors On Protein Turnover In Intact Musclesmentioning
confidence: 99%
“…After stopping the reaction by the addition of 0.5 ml of 8% trichloroacetic acid, the solution was centrifuged at 9,500 ϫ g for 5 min. The supernatant was subjected to absorbance measurement at 366 nm by using a spectrophotometer (Molecular Devices Spectra Max 250) at room temperature as described (34). All assays were done in triplicate.…”
Section: Measurement Of Total Proteases In Mouse Fecesmentioning
confidence: 99%
“…Similarly, Iwata et al (1973) demonstrated the molecular weight of carp alkaline proteinase as 780,000. In constrast, molecular mass of alkaline proteinase from mammalian sources seemed to vary from 30,800 (Dahlmann and Reinauer, 1978) to 120,000 (Dahlmann et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…While some investigators (Lin and Lamer, 1980;Busconi et al, 1984) suggested that the enzyme is sulthydryl dependent, others showed it to be either a metallo (Kozlovskaya and Elyakova, 1975) or a serine proteinase (Kozlovskaya and Elyakova, 1975;Busconi et al, 1984). Differences also seemed to exist between mammalian and invertebrate enzyme (Eguchi and Kuriyama, 1983;Dahlmann and Reinauer, 1978).…”
Section: Introductionmentioning
confidence: 99%